Novel three dimensional topological nodal line semimetallic carbon. (March 2016) - Cheng, Yong; Du, Jinglian; Melnik, Roderick; Kawazoe, Yoshiyuki; Wen, Bin
Abstract: A new cubic three dimensional carbon phase has been predicted by first-principles calculations. This phase is constructed by triangle graphene sheets, and dubbed as sc-C96 . The investigation on its electronic properties has indicated that sc-C96 possesses a topological nodal line semimetal state, which protected by the combination of time reversal and spatial inversion symmetries, and negligible spin–orbit interaction. Due to the cubic symmetry, the Fermi surface of sc-C96 is constituted of three nodal line circles. From the cohesive energy and phonon spectra, we find that sc-C96 is dynamically stable and may be easily synthesized by polymerizing C96 fullerene molecules at a relatively low pressure conditions (∼1 GPa).